Stock exchange mergers : a dynamic correlation analysis on Euronext - Espinosa-Méndez, Christian (2020)
This article investigates the role of Stock Exchange Mergers on stock market return co- movements. Using a dynamic conditional correlation model proposed by Engle (J Bus Econ Stat 20:339–350, 2002), the Euronext Stock Exchange was analyzed, and findings point to an increase in correlation levels of stock return among Euronext unitholders. In short, Euronext stock exchange mergers increased interdependency among these markets, which means that the possibility of diversifying investment risk in these markets is reduced.